A mass transport deposit in the Permian Mackellar Formation, Victoria Group, Antarctica. Issue 2 (3rd April 2022) - Elliot, David H.; Isbell, John L.
ABSTRACT: The Permian Mackellar Formation in the central Transantarctic Mountains is a fine-grained siliciclastic succession, which was deposited in a marine to brackish inland sea (Mackellar Sea) along the hinterland of the Gondwana margin. The Mackellar strata were deposited in an elongate, trough-shaped basin oriented subparallel to the present trend of the Transantarctic Mountains. At the head of the Robb Glacier, the Mackellar beds include, in the middle of the succession, a mass transport deposit, which exhibits folding and thrusting. Structural data (e.g. facing direction and axial planes of overturned folds, orientation and vergence of thrust faults) indicate axial transport down the elongate depositional basin. Unconformable relationships to strata overlying the mass transport deposit suggest reactivation and doming of the deposit following its initial emplacement. Subsequently there was partial collapse of the toe-ward part of the extant deposit along a listric fault, the result of loading by deltaic sandstones of the overlying Fairchild Formation.